Technical and financial evaluation of an emerging thermochemical technology for sustainable management of municipal wastewater sludge - Zvimba, John Ngoni (Water science and technology : a journal of the International Association on Water Pollution Research, 2024)
© 2024 The Authors This is an Open Access article distributed under the terms of the Creative Commons Attribution Licence (CC BY 4.0), which permits copying, adaptation and redistribution, provided the original work is properly cited (http://creativecommons.org/licenses/by/4.0/).